Medical Rapid Prototyping Technologies: State of the Art and Current Limitations for Application in Oral and Maxillofacial Surgery - Winder, John; Bibb, Richard (Journal of oral and maxillofacial surgery, 2005)
We describe state-of-the-art software and hardware requirements for the manufacture of high quality medical models manufactured using medical rapid prototyping. The limitations of medical models, the source of artefacts, and their physical appearance are illustrated along with remedies for their removal. Medical models were built using predominantly stereolithography and fused deposition modeling at both institutions over a period of 6 years. A combined total of 350 models have been produced for a range of maxillofacial, neurosurgical, and orthopedic applications. Stereolithography, fused deposition modeling, computerized numerical milling, and other technologies are described along with computer software requirements. A range of unwanted artefacts that create distortions on medical models have been identified. These include data import, computed tomography gantry distortion, metal, motion, surface roughness due to support structure removal or surface modeling, and image data thresholding. The source of the artefact has been related to the patient, imaging modality performance, or the modeling technology. Discussion as to the significance of the artefacts on clinical use is provided. It is recommended that models of human anatomy generated by medical rapid prototyping are subject to rigorous quality assurance at all stages of the manufacturing process. Clinicians should be aware of potential areas for inaccuracies within models and review the source images in cases where model integrity is in doubt.